2013
DOI: 10.1111/caje.12052
|View full text |Cite
|
Sign up to set email alerts
|

The risk and cost of job loss in Canada, 1978–2008

Abstract: We assess the risk and cost of worker displacement in Canada over the last three decades. We show that neither the risk of job loss nor the short‐term earnings losses of displaced workers trended upwards during that period. However, short‐term earnings losses of workers displaced from manufacturing increased in recent years, as a smaller proportion found a post‐displacement job in that sector. In line with Stevens and Couch and Placzek, we find that high‐seniority workers and individuals with stable labour mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…3 Indeed, some studies of business dynamism have identified large age and education composition effects, but then did not separate trends by gender (Hyatt and Spletzer, 2016;Molloy et al, 2016). Other studies have failed to account for such shifts altogether because business dynamism research often uses data that include little or no information about the composition of the workforce (Davis and Haltiwanger, 2014;Decker et al, 2014;Morissette et al, 2013). 4 Because of these limitations, we hypothesize that recent studies arguing that labour market dynamism has decreased may lead to the inaccurate conclusion that the transformations reported in the flexibilization literature have not translated into a transformation of career trajectories and a decrease in job stability as experienced by workers.…”
Section: Competing Trends Affecting Job Stabilitymentioning
confidence: 99%
“…3 Indeed, some studies of business dynamism have identified large age and education composition effects, but then did not separate trends by gender (Hyatt and Spletzer, 2016;Molloy et al, 2016). Other studies have failed to account for such shifts altogether because business dynamism research often uses data that include little or no information about the composition of the workforce (Davis and Haltiwanger, 2014;Decker et al, 2014;Morissette et al, 2013). 4 Because of these limitations, we hypothesize that recent studies arguing that labour market dynamism has decreased may lead to the inaccurate conclusion that the transformations reported in the flexibilization literature have not translated into a transformation of career trajectories and a decrease in job stability as experienced by workers.…”
Section: Competing Trends Affecting Job Stabilitymentioning
confidence: 99%
“…They are also remarkably consistent with the analysis of Morissette et al . () for Canada. For the UK, Hijzen et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the shock is more permanent or has elements that are likely to be permanent associated with any restructuring, then workers who are permanently displaced from their jobs experience substantial wage losses associated with their loss of fi rm-specifi c human capital. Morissette, Qui, and Chan (2013 ) cite evidence from the literature for Canada that permanent job losses led to earnings losses of around 20 to 30 percent for those who found a job within a year, and around 20 percent after fi ve years after their job loss. In both cases, the losses were higher for women then for men.…”
Section: Determine Early the Novel Versus Permanent Nature Of The Shockmentioning
confidence: 99%